Розвиток тепловозної тяги в СРСР (20-30-ті роки ХХ ст.) - Косовець, Ю. В. (НТУ "ХПІ", 2014)
Стаття присвячена розвитку тепловозної тяги в СРСР у 20-30-х роках ХХ сторіччя. У статті зазначається, що проекти типів тепловозів, які підлягали експериментуванню, розроблялися радянськими інженерами. У роботі брали участь конструкторські бюро локомотивобудівних заводів СРСР, технічне бюро Тепловозної комісії при Народному Комісаріаті шляхів сполучення (НКШС), а також ряд окремих ініціативних груп. Центральне місце в усій роботі зі створення тепловозів і дослідному їх випробовуванні займала Тепловозна комісія при НКШС. Висвітлюється внесок у розвиток тепловозобудування професора Я. М. Гаккеля, інженерів локомотивобудівних заводів: «Червоний путіловець» в Ленінграді, Коломенського заводу, який вже у 1932 р. створив проект серійного тепловоза з індивідуальними тяговими електродвигунами і перейшов до масового його будівництва, а також московського заводу «Динамо» та Харківського електромеханічного заводу.

The article deals with the development of diesel traction in the USSR during the 20-30 years of the ХХ-th century. The article states that the projects of locomotives’ types, which were subject to experimentation, had been developed by Soviet engineers. The work involved design offices of the USSR locomotive-building plants, the technical bureau of diesel commission under the People’s Commissariat of the means of communication (PCMC), as well as a number of special interest groups. Diesel commission under the People’s Commissariat of the means of communication (PCMC), held a central place in all work on the creation of locomotives and their experimental testing. The article highlights the contribution of the professor Ya. M. Hakkelia into the locomotive development, the engineers of locomotive-building plants: “Chervonyi putilovets” in Leningrad, of the Kolomenskyi plant which in 1932 already created a project of a serial locomotive with individual traction motors and passed to its mass construction; as well as the Moscow factory “Dynamo” and Kharkiv electromechanical plant. In the 20-30 years of the twentieth century extensive researchers in the field of creating original locomotives with special thermal cycles, new transmissions, power plants, allowing the use of various sorts of liquid, solid and gaseous fuels were held in the Soviet Union.
The development of diesel traction in the USSR (20 - 30 years of the ХХ-th century)
Keywords: наука; техніка; науково-дослідна робота; НКШС; diesel locomotive; locomotive traction; science; engineering